2015
DOI: 10.1007/s00784-015-1644-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two electronic apex locators on human cadavers

Abstract: Both electronic apex locators can be recommended for clinical use and their accuracy is not affected by SH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…Results of the present study came in full agreement with those of Kaufman and Li in which the irrigants used did not affect the accuracy of different EALs tested (22,23) . Marigo et al (24) found that the accuracy of the Dentaport ZX was not affected by sodium hypochlorite. Duran-Sindreu et al (25) also showed that sodium hypochlorite had no effect on the accuracy of the Root ZX and the iPex.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study came in full agreement with those of Kaufman and Li in which the irrigants used did not affect the accuracy of different EALs tested (22,23) . Marigo et al (24) found that the accuracy of the Dentaport ZX was not affected by sodium hypochlorite. Duran-Sindreu et al (25) also showed that sodium hypochlorite had no effect on the accuracy of the Root ZX and the iPex.…”
Section: Discussionmentioning
confidence: 99%
“…Among foramen locators, Root ZX II (J. Morita, Tokyo, Japan) has received special attention due to its outstanding results, which makes such device a standard for comparison (6)(7)(8)(9)(10). Root ZX II operates an impedance frequencydependent method based on the quotient of impedance measured in each one of the frequencies in which the device works (0.4 and 8 kHz) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Some use the impedance quotient principle, such as Root ZX II (J Morita, Tokyo, Japan) (Altunbas¸ et al, 2014). The Propex II (Dentsply Maillefer, Ballaigues, Switzerland) (Marroquín et al, 2014), the Raypex 6 (VDW GmbH, Munich, Germany) (Marigo et al, 2016) and the Propex Pixi (Dentsply Maillefer) (Üstün et al, 2016) use the square root of the impedances in 2 frequencies. These impedance interpretation mechanisms can affect measurements taken under different clinical conditions (Vaconcelos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%